Echocardiography Detection of High-Risk Patent Foramen Ovale Morphology - Amiliana M Soesanto (The Indonesian Heart Association, 2021)
Patent Foramen Ovale occurs in 25% of the general population1. Several studies suggested that paradoxical embolism through a patent foramen ovale (PFO) correlate with cryptogenic strokes (CS). Many epidemiological and clinical observational studies, showed the association between CS and the presence of PFO. There is still a controversy whether PFO should be closed. The information about PFO morphology might be useful for the management of PFO. This article is discussing a technical information about how echocardiography detects PFO and identifies high risk morphologies for the occurrence of PFO related -stroke.